Avaliação preliminar da associação entre anfotericina e hesperina com oxidantes e células huvec - Manente, Francine Alessandra [UNESP]; da Silva, Ana Flavia Tostes [UNESP]; Schemberger, Josiane Aparecida [UNESP]; Heinrich, Isabella Aparecida [UNESP]; Munhoz, Antonio Carlos Mattar [UNESP]; Beltrame, Flávio Luis [UNESP]; Maia, Danielle Cardoso Geraldo [UNESP]; Urbaczek, Ana Carolina [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Vellosa, José Carlos Rebuglio (My University, 2014)
Amphotericin B (AmB) is drug “gold standard” for the treatment of invasive fungal infections since 1960. However, amphotericin B has high toxicity, which manifests itself most often in the kidneys and in the liver. It is known, since 1985, that self-oxidation of AmB gives different forms of reactive oxidative species and these, being toxic to the cell, would be responsible, in part, by its toxicity. Different studies indicate that hesperidin contributes, through the reduction of oxidative stress, to protect against renal injury generated by ischemia. This fact and the involvement of AmB in the generation of free radicals make it interesting the preliminary evaluation of the effect of hesperidin and AmB (alone or associated) against reactive oxygen species and free radicals, as well as the study on models of cytotoxicity. Front ABTS•+, AmB presented IC50 equal to 0.0124 mg/mL, but when it was associated to hesperidin this value has decreased to 0.0003 mg/mL. Front HOCl, Amb presented IC50 equal to 0.0056, but when it was associated to hesperidin this value has decreased to 0.0023 mg/mL. In the trials with DPPH• and the superoxide anion radical samples were not effective. In the assay with endotelial cell culture (HUVEC cells), the association has decreased cell viability. These preliminary results demonstrate the interaction of the compounds with reactive species as well as indicate the possibility of damage exacerbation by AmB in the presence of antioxidants in an in vitro model.
Preliminary assessment of the association between amphotericin and hesperetin with oxididants and huvec cells
Keywords: Amphotericin B; Cytotoxicity; Hesperidin; Oxidative stress